Respuesta :
Answer:
2x
Step-by-step explanation:
f(x) – g(x)
f(x) = 5x – 3 and g(x) = 3x – 3
f(x)- g(x) = 5x – 3 -( 3x – 3)
Distribute the minus sign
5x -3 -3x+3
Combine like terms
5x-3x-3+3
2x
Answer:
f(x) - g(x) = 2x
Step-by-step explanation:
We have given two functions.
f(x) = 5x-3 and g(x) = 3x-3
We have to find their difference.
f(x)-g(x) = ?
Putting given values, we have
f(x) - g(x) =( 5x-3) - (3x-3)
Distribute negative sign over second parentheses,
f(x) - g(x) = 5x-3 -(3x)-(-3)
f(x) - g(x) = 5x-3-3x+3
f(x) - g(x) = 5x-3x-3+3
Adding like terms, we have
f(x) - g(x) = 2x+0
f(x) - g(x) = 2x which is the answer.